1991
DOI: 10.1007/bf00180583
|View full text |Cite
|
Sign up to set email alerts
|

Microbial metabolism of fluoranthene: isolation and identification of ring fission products

Abstract: The degradation of fluoranthene by pure cultures ofAlcalioenes denitrificans WW1, isolated from contaminated soil samples, was investigated. The strain showed m a x i m u m degradation rates of 0.3 mg fluoranthene/ml per day. A. denitrificans was able to utilize also naphthalene, 1-and 2-methylnaphthalene, phenanthrene, and anthracene as sole carbon sources and to co-metabolize fluorene, pyrene, and benzo(a)anthracene. During growth on fluoranthene in batch culture two metabolic products that were completely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 28 publications
5
56
0
1
Order By: Relevance
“…These data are consistent with data reported in the literature (53). Incubations of DBT with strain F297 yielded products indicative of both aromatic-ring fission and sulfur oxidation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These data are consistent with data reported in the literature (53). Incubations of DBT with strain F297 yielded products indicative of both aromatic-ring fission and sulfur oxidation.…”
Section: Resultssupporting
confidence: 91%
“…These studies have yielded fundamental information about the biodegradability of individual compounds, but little is known of the fate of those compounds in mixtures. It has been recognized that a number of aromatic hydrocarbon degraders have the ability to transform other aromatic substrates to various extents (9,14,15,30,31,33,44,45,47,52,53), suggesting that biotransformations may play important roles in the degradation of environmental mixtures. A number of studies document the degradation of PAC mixtures.…”
mentioning
confidence: 99%
“…Growth on PAH containing four fused aromatic rings (e.g. chrysene, fluoranthene, pyrene, benz[a]anthracene) is somewhat more rare, although organisms are known which can utilize each of these as growth substrates (Heitkamp et al 1988a & b;Churchill et al 1999;Schneider et al 1996;Mueller et al 1990;Boldrin et al 1993;Bastiaens et al 2000, Walter et al 1991, Bouchez et al 1997, Juhasz et al 1997Caldini et al 1995;Weissenfels et al 1991;Vila et al 2001). Currently, very few bacteria have been reported to be capable of growth using solely PAH with five Appendix -14 or more benzene rings (Juhasz et al 1997), although some cases have been reported in which bacteria co-metabolize five-ring PAHs during growth on simpler substrates (Chen and Aitken 1999;Schneider et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Growth on PAH containing four fused aromatic rings (e.g. chrysene, fluoranthene, pyrene, benz[a]anthracene) is somewhat more rare, although organisms are known which can utilize each of these as growth substrates (Heitkamp et al 1988a & b;Churchill et al 1999;Schneider et al 1996;Mueller et al 1990;Boldrin et al 1993;, Walter et al 1991, Bouchez et al 1997, Juhasz et al 1997Caldini et al 1995;Weissenfels et al 1991;Vila et al 2001).…”
Section: Discussionmentioning
confidence: 99%